Description of SARS-CoV-2 Transmission Risk in Indonesian Nurses Due to COVID-19 Exposure - Dayu Laras Wening; Maria Ulfa; Bayu Anggileo Pramesona; Ahmad Veda Yudanto; Momoyo Azuma (Universitas Aisyah Pringsewu, 2022)
Coronavirus disease-2019 is a disease caused by a novel coronavirus called (SARS-CoV-2). In November 10, 2020, confirmed cases of COVID-19 were more than 49 million people recorded by WHO. Indonesian National Nurses Association data on November 12, 2020, showed that 113 Indonesian nurses died from COVID-19. This study aims to describe the handwashing activities, PPE use, work duration, psychological and comorbidities of nurses in Indonesia. It used quantitative methods, purposive sampling and percentage descriptive for statistical analysis. The design was a descriptive survey and online form. There were 112 respondents. The determination of criteria was based on the normal curve. There were 89 people (79.50%) in the low category for the comorbid variable. For work duration, there were 64.30% included in the good category. Using the PPE variable had a high category which is 91 people (81.25%). Respondents who constantly washed their hands were 109 people (97.32%) including in the high class. COVID-19 symptoms found that there were low category 112 people (100%). Most respondents were in the low category of comorbidities. Besides, they had sufficient work duration, they were good in the frequency of using PPE and applying it to handwash. They also had a low category in COVID-19 symptoms. Abstrak: COVID-19 adalah penyakit yang disebabkan oleh novel coronavirus yang disebut (SARS-CoV-2). Pada 10 November 2020, kasus terkonfirmasi COVID-19 tercatat lebih dari 49 juta orang oleh WHO. Data Persatuan Perawat Nasional Indonesia pada 12 November 2020, menunjukkan 113 perawat Indonesia meninggal karena COVID-19. Penelitian ini bertujuan untuk mendeskripsikan aktivitas cuci tangan, penggunaan APD, lama kerja, psikologis dan penyakit penyerta perawat di Indonesia. Metode yang digunakan adalah metode kuantitatif, purposive sampling dan deskriptif persentase untuk analisis statistik. Desainnya adalah survei deskriptif dan formulir online. Ada 112 responden. Penentuan kriteria didasarkan pada kurva normal. Ada 89 orang (79,50%) dalam kategori rendah untuk variabel komorbiditas. Untuk lama kerja terdapat 64,30% termasuk dalam kategori baik. Penggunaan variabel APD memiliki kategori tinggi yaitu 91 orang (81,25%). Responden yang selalu mencuci tangan sebanyak 109 orang (97,32%) termasuk dalam golongan tinggi. Gejala COVID-19 ditemukan kategori rendah sebanyak 112 orang (100%). Sebagian besar responden berada dalam kategori komorbiditas rendah. Selain itu, mereka memiliki durasi kerja yang cukup baik dalam frekuensi penggunaan APD dan penerapannya pada cuci tangan. Mereka juga memiliki kategori rendah dalam gejala COVID-19.